APLIKASI SISTEM PERINGATAN DINI RAWAN PENYAKIT DEMAM BERDARAH BERDASAR ABJ BERBASIS SMS GATEWAY PADA WILAYAH KECAMATAN MRANGGEN (Information Technology and Telematics, 2015)
Abstract : The rain season like this many cases of Population Around Mranggen symptoms and positive Dengue fever sufferers . Especially In children aged range of 9-15 years . The number of patients is quite high in recent months , for ages 9-15 years old in December 2014 reached 20 cases .Most of them could be saved and can be cured . The purpose of this research is to create an early warning system based applications sms gateway dengue fever in the district of Demak Mranggen .This early warning system based on data collection larvae survey conducted in the homes of residents in each water tank, so that the percentage found ABJ ( Figures Free Flick ) . SMS gateway system will provide information to citizens within the scope of the RT if found ABJ value of less than 95 % . Mistakes in entering data larvae survey will affect the value ABJ . Kata Kunci : Peringatan Dini, SMS Gateway, Demam Berdarah, ABJ